Kesenjangan Literasi Digital Orang Tua di Era Digitalisasi Pendidikan: Analisis Integratif Dakwah Bil-Hal dan Tarbiyah Islamiyah - Mutammimah; Siti Nuri Nurhaidah; Ahmad Irfan (Lembaga Yasin AlSys, 2026)
The acceleration of educational digitalization requires the active involvement of parents in supporting their children’s learning process at home. However, some parents continue to face a digital literacy gap encompassing limited technical skills (operational skills gap), weaknesses in evaluating information (critical skills gap), and insufficient understanding of cyber risks (safety and security gap). This study aimed to formulate the conceptual framework of the Integrative Islamic Digital Parenting Framework as an integrative solution grounded in Islamic scholarship to address parents’ digital literacy gaps. The study employed a qualitative approach using library research. Secondary data were obtained from 38 indexed literature sources published between 2020 and 2026, including articles from reputable journals, reports from international organizations such as UNESCO, UNICEF, and the OECD, and foundational works by prominent figures in Islamic education and da‘wah. The data were analyzed through a combination of content analysis and critical-synthesis analysis based on the model of Miles, Huberman, and Saldaña. The results showed that digital literacy gaps cannot be adequately addressed solely through technocratic interventions but require the development of a family digital literacy culture grounded in Islamic values. The Integrative Islamic Digital Parenting Framework synthesizes the pillar of Tarbiyah Islamiyah as a philosophical foundation and a means of fostering moral awareness through the values of mas’uliyah, tabayyun, hifzh al-‘aql, hifzh al-akhlaq, and tawazun, with the pillar of Dakwah bil-Hal as a form of community empowerment praxis implemented through social media da‘wah, parenting classes in mosques, sharia-based modules, assistance from religious counselors, and synergy among the three centers of education. This study concluded that education plays a role in developing parents’ technical and methodological competencies, whereas da‘wah functions to foster ethical awareness and mobilize society. This framework provides a conceptual contribution to the development of Islamic education and digital parenting and offers a practical foundation for families, educational institutions, mosques, and religious counselors in building a digital literacy ecosystem that is safe, critical, and grounded in Islamic values.